2016
DOI: 10.18267/j.pep.534
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Early-Stage Entrepreneurial Discontinuance

Abstract: A high proportion of nascent entrepreneurs do not make it to an operational venture. Even though entrepreneurial exit decisions occur more frequently than many think, the literature on entrepreneurial discontinuance is not much developed. The paper fi rst examines whether factors infl uencing early-stage discontinuance diff er in the Czech Republic in comparison with Western countries. Second, it contributes to existing theories on nascent entrepreneurial activity of "modest majority" low-growth businesses by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Finally, our study is one of the first to verify the nature of the gender gap between family succession and other occupational choices for actual behaviour, vs. entrepreneurial intentions (Zellweger et al 2011;Schröder et al 2011). Longitudinal studies on nascent entrepreneurship confirm that a large proportion of nascent entrepreneurs do not go on to found a business (Lukeš and Zouhar 2016). Thus we contribute to past research by examining actual rather than intended career choice among young people.…”
Section: Theoretical Contributionsmentioning
confidence: 69%
“…Finally, our study is one of the first to verify the nature of the gender gap between family succession and other occupational choices for actual behaviour, vs. entrepreneurial intentions (Zellweger et al 2011;Schröder et al 2011). Longitudinal studies on nascent entrepreneurship confirm that a large proportion of nascent entrepreneurs do not go on to found a business (Lukeš and Zouhar 2016). Thus we contribute to past research by examining actual rather than intended career choice among young people.…”
Section: Theoretical Contributionsmentioning
confidence: 69%
“…Rates of return are non-stationary increasing or decreasing rapidly as a result of an adjustment process [47]. Innovative start-ups are often seen as key drivers of innovation and the creation of new sustainable jobs [48], but due to the dual responsibility of being both new and small, they also face greater obstacles than larger, better-established firms [49]. The advantage of small and young companies is their potential for growth and job creation [50][51][52].…”
Section: Literature Review and Conceptualization Of The Business Incubatormentioning
confidence: 99%
“…The preceding studies presented varying findings about the time spent on the projects. Carter et al (1996), Van Gelderen, Thurik, and Bosma (2005), and Lukeš and Zouhar (2016) suggested that the time spent on the project may have an effect on the outcome status, whereas Gimeno et al (1997) did not find that the number of hours worked influenced the eventual entrepreneurial exits. In our study, the nascent entrepreneurs spent little time on their venture projects and the participants mentioned that they disengaged from the idea in a surprisingly short time: approximately three months after receiving the grant.…”
Section: Meso Levelmentioning
confidence: 96%